Kenakalan Remaja dalam Perspektif Antropologi - Leni, Nurhasanah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2017)
Juvenile Delinquency is a deviant behavior that occurs among adolescents. Juvenile delinquency refers to adolescent behavior that is not in accordance with the norms that live in the community. In terms of juvenile delinquency law is classified into two groups relating to legal norms, namely: (1) delinquency that is immoral and social and is not regulated in law so it can not or is difficult to be classified as a violation of law; (2) delinquency which is unlawful with the settlement in accordance with the law and applicable law is the same as unlawful conduct if committed by an adult. Furthermore culture or culture derived from Sanskrit is buddhayah, which is the plural form of buddhi (mind or intellect) is defined as matters relating to the mind and human reason. In English, culture is called culture, which comes from the Latin word Colere, which is to process or work, so that juvenile delinquency in cultural perspective is very visible relation. Teenagers should be able to get as many adults as possible who would motivate good behavior as well as people who have improved after failing at this stage. The existence of motivation from family, teachers, peers is something that can be done to overcome juvenile delinquency and also good for the development of adolescents. Let us tackle juvenile delinquency wisely. This paper is based on the results of several researchers research.